Excel 2007 data analysis your visual blueprint for creating and analyzing data, charts and PivotTables - Etheridge, Denise (Visual read less, learn more., 2007)
Provides instructions on using Excel to analyze data, covering such topics as creating formulas, using financial functions, organizing worksheet data, working with PivotTables, and automating with macros.